2016
DOI: 10.3109/09513590.2016.1145647
|View full text |Cite
|
Sign up to set email alerts
|

Is the suppressive effect of cyproterone acetate on serum anti-Müllerian-hormone levels in women with polycystic ovary syndrome stronger than under oral contraceptive pill?

Abstract: That any anti-androgen effect could be observed on AMH in our CPA group in addition to the gonadotropin-suppressing effect suggests that either androgens are not involved in AMH regulation or that they act by interfering with gonadotropin effects on granulosa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, many confounding factors may play a role, in particular the positive effect of androgens on the number of growing follicles ( 32 ) and thus on the “granulosa mass.” Caanen et al ( 33 ) observed that administration of androgens as part of female-to-male transitions induced a significant decrease in AMH levels, but the protocol included the use of a GnRH agonist, which might have confused the results by lowering serum FSH level (see below). Finally, the decrease in serum AMH levels in PCOS patients receiving high-dose cyproterone acetate, a progestin with a potent anti-gonadotropic and peripheral anti-androgenic action, was no greater than under other anti-gonadotropic drugs, such as estrogen-progestin contraceptives ( 34 , 35 ). But here again, serum FSH level is low in these situations.…”
Section: Role Of Amh In the Disturbed Folliculogenesis Of Pcosmentioning
confidence: 90%
See 2 more Smart Citations
“…However, many confounding factors may play a role, in particular the positive effect of androgens on the number of growing follicles ( 32 ) and thus on the “granulosa mass.” Caanen et al ( 33 ) observed that administration of androgens as part of female-to-male transitions induced a significant decrease in AMH levels, but the protocol included the use of a GnRH agonist, which might have confused the results by lowering serum FSH level (see below). Finally, the decrease in serum AMH levels in PCOS patients receiving high-dose cyproterone acetate, a progestin with a potent anti-gonadotropic and peripheral anti-androgenic action, was no greater than under other anti-gonadotropic drugs, such as estrogen-progestin contraceptives ( 34 , 35 ). But here again, serum FSH level is low in these situations.…”
Section: Role Of Amh In the Disturbed Folliculogenesis Of Pcosmentioning
confidence: 90%
“…In vivo, Das et al (24) highlighted that the AMH concentration in follicular fluid of 4 to 8 mm antral follicles, was 5 times higher, outside of any ovarian stimulation setting. Catteau-Jonard et al (25) demonstrated increased transcription of the AMH gene and its receptor by quantitative RT-PCR on partially luteinized GCs collected during oocyte puncture for in vitro fertilization in women with PCOS, compared with control women. This increased transcriptional activity was seen in both selected intermediate-sized (8-13 mm mean diameter) and larger dominant follicles (17-22 mm mean diameter).…”
Section: Role Of Amh In the Disturbed Folliculogenesis Of Pcos Is Amhmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the AMH assay kits used differed from those in our study. Plouvier et al [21] reported a significant decrease in follicle numbers per ovary and AMH levels after a 3-month trial of COCs. Fábregues et al [22] reported significant TFC reductions after 6 months of COC use, with a significant positive correlation between TFC and AMH level (rho=0.92 and 0.88; P=0.01 and 0.004, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated whether COCs can modulate PCOM in patients with PCOS [13,[19][20][21][22][23][24][25]. According to Mes-Krowinkel et al [19], the mean ovarian volume, mean ovarian follicle count, and AMH level remarkably decreased in patients using COCs than in patients who had never used COCs after correction for confounding variables such as body mass index, age, waist-to-hip ratio, previous pregnancy, infertility treatment, and ethnicity.…”
Section: Discussionmentioning
confidence: 99%